The properties director's toolkit : creativity, collaboration, and communication for prop shop management in the theatre and performing arts - Strawn, Sandra J.; Schlenker, Lisa (The Focal Press toolkit series, 2018)
"Regardless of your profession, whether you're a Stage Manager or Stagehand, The Focal Press Toolkit Series has you covered. With all the insider secrets, paperwork, and day-to-day details that you could ever need for your chosen profession or specialty, these books provide you with a one-stop-shop to ensure a smooth production process." -- Publisher's description.